Respostas
respondido por:
2
f(x) = ax + b
f(3) = 5
f(-2) = -5
3a + b = 5
-2a + b = -5 *(-1)
3a + b = 5
2a - b = 5
5a = 10
a = 10/5
a = 2
3a + b = 5
3*2 + b = 5
6 + b = 5
b = 5 - 6
b = -1
f(x) = 2x - 1
f(1/2) = 2*(1/2) - 1
f(1/2) = 2/2 - 1
f(1/2) = 1 - 1
f(1/2) = 0
f(3) = 5
f(-2) = -5
3a + b = 5
-2a + b = -5 *(-1)
3a + b = 5
2a - b = 5
5a = 10
a = 10/5
a = 2
3a + b = 5
3*2 + b = 5
6 + b = 5
b = 5 - 6
b = -1
f(x) = 2x - 1
f(1/2) = 2*(1/2) - 1
f(1/2) = 2/2 - 1
f(1/2) = 1 - 1
f(1/2) = 0
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás